2022
DOI: 10.3390/ijms23126584
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Tissue Investigation of Molecular Targets and Physiological Functions of Nsun6 Using Knockout Mice

Abstract: The 5-methylcytosine (m5C) modification on an mRNA molecule is deposited by Nsun2 and its paralog Nsun6. While the physiological functions of Nsun2 have been carefully studied using gene knockout (KO) mice, the physiological functions of Nsun6 remain elusive. In this study, we generated an Nsun6-KO mouse strain, which exhibited no apparent phenotype in both the development and adult stages as compared to wild-type mice. Taking advantage of this mouse strain, we identified 80 high-confident Nsun6-dependent m5C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…However, the upstream genes that regulate NM23-H1 expression in lung cancer are not well understood [ 31 ]. Our findings suggest that over-expression of NSUN6 attenuates cell proliferation, migration, and EMT of lung cancer by regulating NM23-H1 by binding to its 3′-UTR via m5C modification, similar to other studies which have demonstrated the binding of NSUN6 to target genes through modification of m5C [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, the upstream genes that regulate NM23-H1 expression in lung cancer are not well understood [ 31 ]. Our findings suggest that over-expression of NSUN6 attenuates cell proliferation, migration, and EMT of lung cancer by regulating NM23-H1 by binding to its 3′-UTR via m5C modification, similar to other studies which have demonstrated the binding of NSUN6 to target genes through modification of m5C [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…For instance, NSUN6 is mainly expressed in Tregs in TNBC ( 36 ), but in exhausted CD8+ T cells, proliferating T cells and myofibroblasts in CRC ( 80 ). In addition, NSUN6 is also related to the promotion of the cell cycle ( 82 ), infiltration of B cells, CD4+ T cells and CD8+ T cells ( 36 , 80 ), and formation of antibody-secreting plasma cells ( 83 ). NSUN7 methylates eRNA, a noncoding RNA associated with transcription modulation, and enhances the expression of mRNAs coding for Pfkl, Sirt5, Idh3b and Hmox2 in a peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α)-dependent manner.…”
Section: The Mechanism and Basic Biological Functions Of M ...mentioning
confidence: 99%
“…Genes associated with m 5 C RNA modifications in B cells include NSUN2, NSUN6, DNMT3A, TET1 and TET3 ( 37 , 38 , 80 ). Specifically, although NSUN6 is dispensable for germinal center (GC) B-cell formation, it plays vital roles in the formation of antibody-secreting plasma cells ( 83 ).…”
Section: C Rna Modification In Immune Cellsmentioning
confidence: 99%
“…NSUN5 can bind to viral RNA and enhance the RNA-sensing function of RIG-I, functioning as a cardinal receptor ( 113 ). NSUN6 is involved in plasma cell formation ( 114 ). Meanwhile, DNMT2 responds to infection and relies on the dynamic installation of m 5 C to regulate the expression of antiviral genes, facilitating an efficient response ( 115 , 116 ).…”
Section: Non-m 6 a Rna Modifications In Antiviral ...mentioning
confidence: 99%